Associação entre o consumo de ultraprocessados e características de hiperatividade em adolescentes: estudo longitudinal - Ferreira, Ricardo Campos (Universidade do Vale do Rio dos Sinos, 2020)
This longitudinal study aims to verify the association between consumption of ultra-processed foods and the presence of characteristics of hyperactivity in adolescents. The study consists of an analysis of secondary data from a larger study, which has a randomized field trial design with children recruited at birth. At birth, the mother-child pairs were randomized into an intervention and control group, and the intervention group was submitted to a program of dietary guidelines, related to the guidelines developed by the General Coordination of Food and Nutrition Policy of the Ministry of Health called: “Ten Steps to Healthy Eating for Children Under Two Years”. The study comprised four phases of data collection, through home visits through interviews with mothers. The analyzes of the present study considered the data collected at 3-4, 7-8 and 12-13 years and did not take into account the initial group that the child was part of. Two 24-hour recall surveys were conducted with each child, and from them the consumption of ultra-processed grams, kcal and percentage of energy in relation to the total energy value of the diet was calculated. The SDQ skills and difficulties questionnaire version for adolescents was applied, an instrument that tracks mental health problems and was answered by the participants themselves (version intended for 11-16-year old). As for the results with statistical significance, it was observed that the consumption of kcal from ultra-processed foods at 4 years of age and being overweight at 12 years of age are associated with the presence of characteristics of hyperactivity in adolescence (p = 0.002 and p = 0.034). This study shows that the consumption of an unhealthy diet in childhood can impact behavioral aspects in adolescence, which reinforces the importance of early action aimed at the development of healthy eating habits.
Keywords: Dieta; Ultraprocessados; Hiperatividade; Adolescentes; Estudo longitudinal; Diet; Ultra-processed; Hyperactivity; Teens; Longitudinal study; ACCNPQ::Ciências da Saúde::Nutrição